Analisis Faktor-faktor yang Mempengaruhi Minat Mahasiswa Batam untuk Berinventasi di Pasar Modal - Lina; Dian Efriyenti (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2025)
Students are a primary target for the Indonesia Stock Exchange in efforts to increase the number of young investors. This study aims to evaluate the influence of minimum capital, financial literacy, and stock returns on the investment interest of accounting students in the city of Batam. The method used is quantitative, with a research population of 100 accounting students. A sample was taken using Slovin's formula, resulting in 96 respondents. The sampling technique applied is simple random sampling. Data collection was conducted through a questionnaire that was validated and tested for reliability before distribution. Data analysis was performed using multiple linear regression tests. The results show that minimum capital significantly influences the investment interest of accounting students in Batam. Meanwhile, financial literacy and stock returns have an influence, but it is not significant in affecting the investment interest of accounting students in the city of Batam.